2013
DOI: 10.1177/1071100713477386
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Dorsiflexion Angle and Plantar Pressure Following Arthrodesis of the First Metatarsophalangeal Joint

Abstract: Significant increase in plantar pressure under the first metatarsal head may be avoided by performing the arthrodesis of the 1MTTP joint below 30° and 15° for the radiological and clinical dorsiflexion angles, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…It is known from the literature that the optimal DFA of the hallux ranges between 20 degrees and 25 degrees, with higher DFAs causing higher pressures beneath the first metatarsal. 1,3 In our opinion, decreased PP or PTI beneath the first metatarsal head was not observed since patients included in this study had an average DFA of 30 degrees.…”
Section: Discussionmentioning
confidence: 76%
“…It is known from the literature that the optimal DFA of the hallux ranges between 20 degrees and 25 degrees, with higher DFAs causing higher pressures beneath the first metatarsal. 1,3 In our opinion, decreased PP or PTI beneath the first metatarsal head was not observed since patients included in this study had an average DFA of 30 degrees.…”
Section: Discussionmentioning
confidence: 76%
“…15 According to these authors, an increase in DFA will increase the pressure on the first metatarsal head or the pressure on the dorsal side of the interphalangeal joint of the hallux (IF1). 16,17 However, Stevens et al 18 reported a 30° DFA in their series of patients, in which they performed an analysis of gait pressures and concluded that first MTPJ arthrodesis increased pressure on the minor metatarsals and descended on the first metatarsus. Brodsky et al 19 supplied documentary evidence about a small DFA (13.2°); excellent clinical results were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The increased MF and PP under M3 may be associated with the decreased range of motion (ROM) under M3 [ 23 ]. The dorsiflexion angle was positively correlated with plantar pressures under M3 [ 30 ]. In our investigation, increased MF and PP may be associated with decreased ROM under M3.…”
Section: Discussionmentioning
confidence: 99%